2008
DOI: 10.3166/remn.17.169-197
|View full text |Cite
|
Sign up to set email alerts
|

Multi-level gradient-based methods and parametrisation in aerodynamic shape design

Abstract: ABSTRACT. The present study focuses on multi-level approaches in the context

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…This approach is akin to a multi-grid method for parameterisation and was first used in an aerodynamic optimisation setting by Beux and Dervieux [18]. It has since been applied to a range of aerofoil optimisation problems using a variety of different parameterisation frameworks such as Bèzier curves [19,20,21,22], Bèzier surface FFD [23,24,25,26], RBFs [27] and B-Splines with a knot insertion algorithm [28,29]. In general, they have shown that implementation of progressive nested parameterisations can improve the convergence rate, robustness and final solution of an optimisation procedure.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is akin to a multi-grid method for parameterisation and was first used in an aerodynamic optimisation setting by Beux and Dervieux [18]. It has since been applied to a range of aerofoil optimisation problems using a variety of different parameterisation frameworks such as Bèzier curves [19,20,21,22], Bèzier surface FFD [23,24,25,26], RBFs [27] and B-Splines with a knot insertion algorithm [28,29]. In general, they have shown that implementation of progressive nested parameterisations can improve the convergence rate, robustness and final solution of an optimisation procedure.…”
Section: Introductionmentioning
confidence: 99%
“…This approach was first used in an aerodynamic optimisation setting by Beux and Dervieux 18 and has since been applied to a range of aerofoil optimisation problems using a variety of different parameterisation frameworks such as Bèzier curves [19][20][21][22] , Bèzier surface FFD [23][24][25][26] , RBFs 27 and B-splines with a knot insertion algorithm 28,29 . In general, it was shown that implementation of multi-level nested parameterisations can improve the convergence rate, robustness and final solution of an optimisation procedure.…”
Section: Introductionmentioning
confidence: 99%
“…increasing the number of design variables) occurs at regular intervals during the optimization process, but it is hard to identify a clear signal for this procedure. Some authors 1,3 argue that when the number of design variables is small, a small number of optimization iterations is enough and full convergence is unnecessary, since these optimization cycles are only intermediate steps. However others 32,33 point out that the optimizations at the first few cycles should be driven sufficiently close to the optimal shape that the current shape can provide a good start for subsequent optimizations.…”
Section: Optimization Proceduresmentioning
confidence: 99%
“…One well recognized problem in aerodynamic shape optimization is attributed to an excessive number of design variables. A number of authors [1][2][3] have pointed out that the presence of a large number of design variables results in poor performance for most existing optimization algorithms. Thus, it is essential to include a limited number of critical design variables in an optimization, and the challenge of choosing design variables is faced by a designer.…”
Section: Introductionmentioning
confidence: 99%